A radiographic investigation of cervical spine kinematics when reading a tablet in a reclined trunk position. (July 2018) - Douglas, Ethan C.; Gallagher, Kaitlin M.
Abstract: The purpose of this study was to use radiographic measurements to compare cervical spine kinematics in various tablet computer reading postures. Radiographs were taken of twenty-two participants reading a tablet computer in five different postures. The lower cervical spine was more flexed in the semi-reclined (-8.2 ± 3.8°) and the reclined (-14.9 ± 4.0°) tablet positions compared to an upright (-4.43 ± 4.8°) tablet posture. Of the tablet reading positions, the reclined position had the lowest gravitational moment arm (5.2 ± 2.3 cm) and a skull angle closest to neutral (-9.4 ± 11.4°), while exhibiting the largest extension in the C1-C2 joint (34.4 ± 9.1°). Altering trunk position when reading a tablet could reduce the load required to support the head, but could put the head in a more forward head posture, stretch the cervical extensor muscles, and potentially result in pain. Highlights: Radiographic examination of the cervical spine while reading from a tablet. Increased posterior trunk rotation led to greater lower cervical flexion. Gravitational moment arm was reduced by increasing posterior trunk rotation. Participants could be using different strategies to achieve similar neck angles. Reading a tablet with a reclined trunk saw both benefits and additional risks.